EFFECTS OF ESSENTIAL OILS ON THE FEEDING CHOICE BY MOOSE - Edlich, Sabine Christina; Stolter, Caroline (Lakehead University, 2012)
Moose (Alces alces) browse on coniferous tree species to different extents during winter; for example, Norway spruce (Picea abies) is avoided, Scots pine (Pinus sylvestris) is preferred, with juniper (Juniperus communis) of intermediate use. Conifers contain essential oils that may act as feeding deterrents, thereby reducing food intake by herbivores. Because essential oils are volatile, our objectives were to determine if 1) odour plays a role in the food choice by moose, 2) whether single monoterpenes act as feeding deterrents, and 3) if this might be a mechanism used to discriminate against unpalatable plants. The essential oils of Norway spruce and juniper and 2 monoterpenes (limonene and camphene) predominant in the essential oil of Norway spruce were tested for their potential as deterrents in feeding trials. Deterrence was assessed in food choice experiments by measuring the time spent feeding on food treated with the different odours associated with these compounds. There was no statistical evidence that food treated with the essential oils of spruce and juniper and single monoterpenes from Norway spruce were avoided by moose. However, our data indicate that the essential oil of Norway spruce probably has a negative effect on moose foraging because of the large absolute difference in feeding time between treatments and that overall, odour had a significant effect on feeding time. Because our experimental design may have influenced the results, we suggest research approaches to better measure deterrence effects.